Flexural strengthening of reinforced concrete beams using precast sifcon laminates - Balaji, S.; Thirugnanam, G.S. (Journal of Structural Engineering, 2024)
Slurry infiltrated fibrous concrete (SIFCON) is a novel type of high performance fibre reinforced concrete made by infiltrating steel fibre bed with a specially designed cement based slurry. Laboratory experiments have shown that SIFCON is an innovative construction material possessing both high strength and large ductility. In the present study, the use of SIFCON has been investigated as an externally bonded strengthening material on reinforced concrete beams. The experimental programme has been carried out to study the behavior of flexural RC beams with precast SIFCON laminates. A total number of twelve specimens of size 100mm × 150 mm × 1700 mm corresponding to four test series are cast and tested under static loading to study the load deformation behavior and ductility associated parameters. The concrete mix for RC beams has been designed to obtain a concrete grade of M30. For laminates the fibre volume fraction was 9%. The steel fibres used in the study were round crimpled fibres having 0.5 mm diameter and aspect ratio of 60. Results indicate that the strengthening of RC beams with SIFCON laminates has significantly improved the cracking behavior in terms of significant increase in first crack load and the formation of larger number of finer cracks. The stiffness, ductility and energy absorption are found to be increase to a great extent when the beams are strengthened by three face confinement (bottom and side faces).